Dynamics of indicators of oxidative stress and bone metabolism during treatment with thiotriazolin in patients with combined type 2 diabetes mellitus and osteoporosis course who reside in anthropogenic pressure conditions - Kryvenko, Vitaliy; Borodavko, Olga (ScienceRise: Medical Science, 2019)
The aim of the study. To investigate the effect of thiotriazolin on oxidative stress and bone metabolism in patients with a combined course of type 2 diabetes and osteoporosis, who permanently reside in industrial region. Materials and methods. On the basis of the educational and scientific medical center "University Hospital" of Zaporizhzhia State Medical University, 44 patients with combined course of type 2 diabetes and osteoporosis, who permanently resided in Zaporizhzhia, were examined for the period from 2016–2017. 22 patients received standard basic therapy for type 2 diabetes and osteoporosis, and 22 patients additionally received thiotriazolin. Patient groups were comparable in age, sex, and duration of type 2 diabetes mellitus. All patients studied the concentration of markers of oxidative stress (nitrotyrosine, 8-hydroxyguanine) and bone metabolism (osteocalcin and deoxypyridinoline). Results. Patients with a combined course of type 2 diabetes mellitus and osteoporosis who received basic therapy with thiotriazolin supplementation registered a significant decrease in the concentration of oxidative stress. Thus, in patients of the second group, there was a significant decrease in the serum level of nitrotyrosine by 5.5 times (p<0.05) and 8-hydroxyguanine by 2.1 times (p<0.05). When evaluating markers of bone metabolism in patients of the second group, the level of osteocalcin increased by 24 % (p<0.05), and the concentration of deoxypyridinoline significantly decreased in individuals of both groups, but in the group with the addition of thiotriazolin, its rate decreased by 30%, and in the first group only 16 % (p<0.05). Conclusions. In patients with a combined course of type 2 diabetes and osteoporosis, which, in addition to basic therapy, thiotriazolin was included, a significant decrease in markers of oxidative stress was registered in a daily dose of 600 mg for 3 months. Under the influence of basic therapy with the addition of thiotrazoline, a significant increase in bone formation and a decrease in bone resorption were observed in patients with a combined course of type 2 diabetes and osteoporosis